Correlation between Social Support and Anxiety among First Year Female Medical Student of Faculty of Medicine Sebelas Maret University in 2015 - Nisrina Mutia Ariani; Mohammad Fanani; Siti Aisyah (Nexus Kedokteran Klinik, 2016)
Introduction: 18 25 years old university student is included into adolescent. Adolescent are susceptible of mental disorder, and one of the most common is anxiety. Female adolescent have the risk to anxiety two times higher. Anxiety can cause distortion of perception that can disturb the process of learning. Medical student have a greater risk to develop anxiety. To deal with stressor from the outside, an individual needs mental tenacity, and one of the factors that causing anxiety is social support. This research is aiming to understand the correlation between Social Support and Anxiety among First Year Female Medical Student in Faculty of Medicine Sebelas Maret University. Methods: An observational analytics strategy and the cross-sectional study were adopted. This study had been done on November 2015 in Faculty of Medicine Sebelas Maret University. The subject was first year female medical student. This research used purposive sampling, and was done with questionnaires. There are five parts of the questionnaire (1) Informed consent; (2) Personal Information; (3) L-MMPI Questionnaire; (4) Taylor Manifest Anxiety Scale Questionnaire; (5) Interpersonal Support Evaluation List Questionnaire. Inclusion and exclusion were applied. The number of total sample was 102. Data analyzed using Kolmorgov-Smirnov and Pearson using SPSS Statistics. Results: Pearson's Product-Moment Correlation using SPSS Statistics suggest that the correlation coefficient was -0.24 (p=0.015). The value p < 0.05 suggests that there was specific correlation between social support and anxiety. The negative symbol suggest that higher levels of social support were related to lower levels of anxiety of First Year Female Medical Student in Faculty of Medicine Sebelas Maret University. Conclusion: There was specific correlation between social support and anxiety of First Year Female Medical Student in Faculty of Medicine Sebelas Maret University. There was specific correlation that suggests higher levels of social support were related to lower levels of anxiety. Keywords: social support, anxiety, female medical student